2020
DOI: 10.1007/s40194-020-00930-2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the manufacturing efficiency of WAAM by advanced cooling strategies

Abstract: Wire- and arc-based additive manufacturing (WAAM) is a promising technology for large-scale additive manufacturing of metallic components. However, due to the high heat input by the electric arc, interpass cooling time decelerates the average manufacturing speed. Since future applications aim to the production of large structural steel components, the manufacturing speed is a key parameter to make WAAM usable for civil engineering. Within the scope of this paper, different process cooling strategies are weighe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The yield and tensile strength showed to be not affected by active cooling. Reisgen et al [18] evaluated different cooling strategies using steel (G3Si1). Active cooling via water bath, high-pressure air, and aerosol were compared regarding the resulting cooling times, microstructure, and hardness.…”
Section: Thermal Influences During Waam Of Steel Structuresmentioning
confidence: 99%
“…The yield and tensile strength showed to be not affected by active cooling. Reisgen et al [18] evaluated different cooling strategies using steel (G3Si1). Active cooling via water bath, high-pressure air, and aerosol were compared regarding the resulting cooling times, microstructure, and hardness.…”
Section: Thermal Influences During Waam Of Steel Structuresmentioning
confidence: 99%
“…A combination of high-pressure air cooling and a watercooled base table is chosen to avoid any issues normally associated with electrical safety and maintenance requirements of a water cooling system, as investigated in [14]. Owing to longer cooling times (t 8/5 ), the proposed high-pressure air cooling allows for fewer changes in microstructure and hardness.…”
Section: The Cooling Systemmentioning
confidence: 99%
“…At the same time the build-up time was reduced by more than a half. Reisgen et al [14] compared water bath cooling, high-pressure air cooling and aerosol cooling of the structural steel deposit using the GMA process. They found that the water bath cooling has the highest cooling effect although it makes the manipulation of the workpiece more difficult and constrains the degrees of freedom of the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, WAAM productivity can be increased by adopting an interlayer cooling strategy that limits idle time by forcing the cooling of the lastly deposited layer. [ 4 ] Toward this aim, different methodologies have been studied: water bath, high‐pressure air, aerosol, CO 2 gas jet, and a combined system with an air jet and a water‐cooled platform. [ 4–11 ] However, when thinking about the industrial applicability of cooling strategies, the one performed with a high‐pressure air jet is the most feasible, especially in case of large‐scale structures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Toward this aim, different methodologies have been studied: water bath, high‐pressure air, aerosol, CO 2 gas jet, and a combined system with an air jet and a water‐cooled platform. [ 4–11 ] However, when thinking about the industrial applicability of cooling strategies, the one performed with a high‐pressure air jet is the most feasible, especially in case of large‐scale structures. Currently, the issue of forced interlayer cooling has been mainly addressed process‐wise with the support of numerical simulations [ 5,6 ] or with the aim to reduce parts’ distortions, [ 7,8 ] whereas limited effort has been devoted to assess the effect of different cooling conditions on the final mechanical properties of printed parts.…”
Section: Introductionmentioning
confidence: 99%